Self and Society. - Kremer, Alexander. (Value Inquiry Book Series, 2009)
This book is the fourth volume of selected papers from the Central European Pragmatist Forum (CEPF). It deals with the general question of self and society, and the papers are organized into sections on Self and History, Self and Society, Self and Politics, Self and Neopragmatism, and an Interview with Richard Rorty. The authors are among the leading specialists in American philosophy from universities across the US and in Central and Eastern Europe.